PENGARUH KECERDASAN EMOSIONAL TERHADAP RGANIZATIONAL CITIZENSHIP BEHAVIORD DAN DAMPAKNYA PADA KINERJA PERAWAT RUMAH SAKIT UMUM ANUTAPURA & RUMAH SAKIT UNDATA PALU - Ibrahim, Ibrahim (Katalogis, 2013)
The objectives of this research are to know and analyze: (1) the effect of emotional quotient on organizational citizenship behavior of nurse’s at Anutapura Public Hospital and Undata Hospital, (2) the effect of organizational citizenship behavior on nurse‘s performance, (3) the effect of emotional quotient on nurse‘s performance, (4) the difference of emotional quotient, organizational citizenship behavior, and performance between nurse’s at Anutapura Public Hospital and Undata Hospital. This is an explanatory research that examines relationships among investigated variables involving 157 nurses who have been selected using proportional random sampling technique. Based on the result of Structural Equation Modeling (SEM), it shows that: (1) emotional quotient performs significant effect on organizational citizenship behavior of nurse’s at Anutapura Public Hospital and Undata Hospital, (2) organizational citizenship behavior performs significant effect on nurse‘s performance at Anutapura Public Hospital and Undata Hospital, (3) emotional quotient performs significant effect on nurse‘s performance at Anutupura Public Hospital and Undatu Hospital. In addition, based on the result of independent sample T-test, it shows that: (1) there are significant differences of emotional quotient and organizational citizenship behavior between nurse's at Anutapura Public Hospital and Undata Hospital, (2) there is no significant difference of performance between nurses at Anutapura Public Hospital and Undata Hospital.